Characteristics of Isolates of Pseudomonas aeruginosa and Serratia marcescens Associated With Post-harvest Fuzi (Aconitum carmichaelii) Rot and Their Novel Loop-Mediated Isothermal Amplification Detection Methods - Fu, Meng; Zhang, Xin; Chen, Bei; Li, Mingzhu; Zhang, Guoyan; Cui, Langjun (Frontiers in Microbiology, 2021)
Fuzi (the lateral root of Aconitum carmichaelii Debx.) is a traditional Chinese medice that is cultivated in more than eight provinces in China. However, it can be easily devastated by post-harvest rot, causing huge losses. Therefore, it is extremely important that the primary causal pathogens of post-harvest Fuzi rot are identified and appropriate detection methods for them are developed to prevent and control losses. In this study, two bacterial strains (X1 and X2) were isolated from rotten post-harvest Fuzi. Based on their morphological, physiological, and biochemical characteristics, housekeeping gene homologies, and matrix-assisted laser desorption ionization/time-of-flight mass spectrometry (MALDI-TOF MS) results, these isolates were identified as Pseudomonas aeruginosa and Serratia marcescens. The pathogenicities of these isolates were confirmed by fulfilling Koch’s postulates demonstrating that they were post-harvest Fuzi rot pathogens. Two loop-mediated isothermal amplification (LAMP) methods targeting the gyrase B subunit (gyrB) gene of P. aeruginosa and the phosphatidylinositol glycan C (pigC) gene of S. marcescens were successfully developed, and it was found that the target genes were highly specific to the two pathogens. These LAMP methods were used to detect P. aeruginosa and S. marcescens in 46 naturally occurring Fuzi and their associated rhizosphere soil samples of unknown etiology. The two bacterial assays were positive in some healthy and rotten samples and could be accomplished within 1 h at 65 °C without the need for complicated, expensive instruments. To our knowledge, this is the first report of P. aeruginosa and S. marcescens causing post-harvest Fuzi rot. The newly developed methods are expected to have applications in point-of-care testing for the two pathogens under different Fuzi planting procedures and will significantly contribute to the control and prevention of Fuzi rot.